2016
DOI: 10.1590/0103-6440201600385
|View full text |Cite
|
Sign up to set email alerts
|

In Situ and In Vitro Effects of Two Bleaching Treatments on Human Enamel Hardness

Abstract: The aim of this study was to evaluate in vitro and in situ the effects of two bleaching treatments on human enamel surface microhardness. Sixty enamel slabs from recently extracted thirty molars were used. The specimens were polished with sandpapers under water-cooling. The enamel samples were randomly divided in four groups, treated with 10% hydrogen peroxide (HP) or Whitening Strips (WS) containing 10% hydrogen peroxide and using two conditions: in vitro or in situ model. For in situ condition, six volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
(28 reference statements)
0
9
1
Order By: Relevance
“…Various researches have evaluated the effectiveness in relation to color change, tooth sensitivity and safety of bleaching gels, by means of diverse techniques (mediate and immediate); concentrations of diverse hydrogen peroxide, carbamide peroxide, with and without sources of light activation for potentiating the bleaching gel (PAULA et al, 2015;DAWSON et al, 2011;BERGER et al, 2012;KEMALOGLU et al, 2014;HENN-DONASSOLLO et al, 2016). However, in this study, we sought to analyze two different bleaching gels with the same concentration of hydrogen peroxide, using the same bleaching technique, with the only difference being the clinical time of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Various researches have evaluated the effectiveness in relation to color change, tooth sensitivity and safety of bleaching gels, by means of diverse techniques (mediate and immediate); concentrations of diverse hydrogen peroxide, carbamide peroxide, with and without sources of light activation for potentiating the bleaching gel (PAULA et al, 2015;DAWSON et al, 2011;BERGER et al, 2012;KEMALOGLU et al, 2014;HENN-DONASSOLLO et al, 2016). However, in this study, we sought to analyze two different bleaching gels with the same concentration of hydrogen peroxide, using the same bleaching technique, with the only difference being the clinical time of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there is a change in the structure of enamel and the bond strength when the teeth are exposed to bleaching agents. 2,3 The reduction in bond strength has been related to morphological changes in mineralized tissues. Bleaching agents also affect the collagen network of dentin, resulting in denaturing and relative instability of the dentin organic matrix, thereby decreasing the bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…1 Tooth whitening or bleaching has become one of the most common procedures in this branch of dentistry, adopted by numerous dentists and their patients as the method of choice to improve tooth appearance due to its being minimally-invasive, easy, efficient and effective. 2,3 The number of patients seeking orthodontic treatment who might have a history of tooth bleaching is increasing because, following previous procedures, they usually tend to be conscious of orthodontic problems and desire treatment. 4 Unfortunately, bleaching may lead to a reduction in orthodontic bracket bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available in vitro dental whitening protocols perform the dental whitening procedure at times greater than 96 hours, making them more time consuming ( 17 , 18 ). This study aims to develop a protocol that performs dental bleaching procedures in vitro in a cheap, fast and accessible manner.…”
Section: Introductionmentioning
confidence: 99%